A personal view oil pipeline relining with hdpe: Experimental and calculation challenge - Frontini, Patricia Maria (2018)
Nowadays the use of polymers in the gas and oil transportation industry is widely spread. One of their main uses is as lining materials for oil pipe - lines. The liners consist of a free-standing thermoplastic pipe that is inserted into an existing steel host pipe. High Density Polyethylene (HDPE) is the most frequently thermoplastic used for this application. The corrosion-resistant barrier provided by an advanced polyethylene liner would extend the pipe - line’s life, as well as provide dual containment, helping to improve pipeline environmental safety. Moreover, the entire rehabilitation of a deteriorated pipeline via HDPE relining can be accomplished in few months avoiding costly complete pipeline replacement. Internal pipeline rehabilitation has been in common use for approximately 30 years in USA and Canada, and it is currently extensively used in South America.